KRAMA LANGUAGE AS EDUCATIONAL COMMUNICATION AT JUNIOR HIGH SCHOOL ISLAM PRESTASI AL MUBTADI-IEN BANTUL IN ISLAMIC EDUCATION PERSPECTIVE - Moh Iqbal Abdullah Kafi; Sukiman (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2020)
Cases of verbal bullying are still prevalent among students in schools. Therefore, efforts are needed through various approaches to overcome the problem. One of the efforts that can be done is through the habituation of krama language in the school environment. This article aims to analyze the application of krama language as an educational communication ethic in Junior High School Islam Prestasi Al Mubtadi-ien Bantul in the perspective of Islamic education. The important issue discussed is the purpose and form of application of manners language as educational communication and its impact on the formation of student behavior seen from the perspective of Islamic education. This research is qualitative research using a phenomenological approach in Junior High School Islam Prestasi Al Mubtadi-ien Bantul, Yogyakarta. Data collection using observation, interviews, and documentation. Data analysis uses data reduction, data exposure, and inference/verification measures. Data collection using observation, interviews, and documentation. Data analysis uses data reduction, data exposure, and inference/verification measures. The results of this study showed: First, the form of educational communication ethics applied in Junior High School Islam Prestasi Al Mubtadi-ien Bantul is based on the cultural values of krama language carried out during the implementation of the learning process in the classroom and in interactions outside the classroom in the school environment. The application of krama language aims to shape student behavior and participate in preserving the culture of krama language as is done in a pesantren environment. Second, the application of communication ethics using Javanese culture krama in Junior High School Islam Prestasi Al Mubtadi-ien Bantul is considered to have provided positive benefits and impacts for students. Third, from the perspective of Islamic education, the application of krama language culture in Junior High School Islam Prestasi Al Mubtadi-ien Bantul is very relevant. Islam is very concerned about the ethical issue of communication. Islam teaches the delivery of information messages to citizens using good language, friendly and polite.